Pouvoir éducatif et frontières du moi - Éric Dubreucq (Nantes Université, 2019)
There are external borders between nations, but also the inner ones which circumscribe and constitute the education of the ego. A genealogy of the ego spaces will show that it oscillates between three types of educational prescriptions: one stows it in hierarchical social "circles" (Durkheim), one serch to extract it from the "valley" where it's confined by its egocentration (Piaget), one placed in a "medium" to be socialized (Cousinet). The inner boundaries of the self are delimited at the intersection of the three educational strategies of integration, liberation and socialization.